English Didactics in Norway 30 years of doctoral research - Lisbeth M Brevik (Scandinavian University Press (Universitetsforlaget), 2019)
This edited volume presents 30 years of English didactics research (1988-2017) in Norway. As a collection of chapters, each representing a doctoral study, the book is a complete overview of all doctoral research within the field. Each study discusses empirical, methodological and theoretical contributions, and implications for teaching English as a second or additional language (L2) today.